2013
DOI: 10.1007/s00249-013-0940-y
|View full text |Cite
|
Sign up to set email alerts
|

External protons destabilize the activated voltage sensor in hERG channels

Abstract: Extracellular acidosis shifts hERG channel activation to more depolarized potentials and accelerates channel deactivation; however, the mechanisms underlying these effects are unclear. External divalent cations, e.g., Ca(2+) and Cd(2+), mimic these effects and coordinate within a metal ion binding pocket composed of three acidic residues in hERG: D456 and D460 in S2 and D509 in S3. A common mechanism may underlie divalent cation and proton effects on hERG gating. Using two-electrode voltage clamp, we show prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 43 publications
3
28
1
Order By: Relevance
“…Double mutant cyclic analysis revealed energetic coupling between R531 and D456, D460, and D509 during activation and with D411 and D466 through a cooperative ionic-pairing interaction mechanism (Piper et al, 2008). Accessibility studies have also revealed that D460 and D509 stabilize the activated state (Liu et al, 2003), which is consistent with observations that neutralization of any of the acidic charges accelerates deactivation kinetics, likely by disrupting electrostatic interactions with S4 basic residues (Liu et al, 2003;Fernandez et al, 2005;Piper et al, 2008;Shi et al, 2014). Interestingly, disruption of the electrostatic pairing involving D509, either by protonation or alanine substitution, destabilizes the relaxed state of the voltage sensor leading to the loss of hysteresis and accelerated deactivation (Shi et al, 2019).…”
Section: The Voltage Sensor Domain (S1-s4)supporting
confidence: 76%
See 2 more Smart Citations
“…Double mutant cyclic analysis revealed energetic coupling between R531 and D456, D460, and D509 during activation and with D411 and D466 through a cooperative ionic-pairing interaction mechanism (Piper et al, 2008). Accessibility studies have also revealed that D460 and D509 stabilize the activated state (Liu et al, 2003), which is consistent with observations that neutralization of any of the acidic charges accelerates deactivation kinetics, likely by disrupting electrostatic interactions with S4 basic residues (Liu et al, 2003;Fernandez et al, 2005;Piper et al, 2008;Shi et al, 2014). Interestingly, disruption of the electrostatic pairing involving D509, either by protonation or alanine substitution, destabilizes the relaxed state of the voltage sensor leading to the loss of hysteresis and accelerated deactivation (Shi et al, 2019).…”
Section: The Voltage Sensor Domain (S1-s4)supporting
confidence: 76%
“…The Relaxed State of the Voltage Sensor Is Destabilized by Extracellular Protons hERG channel deactivation kinetics are sensitive to changes in the extracellular proton concentration and numerous studies have shown that acidosis accelerates deactivation rate (Anumonwo et al, 1999;Bérubé et al, 1999;Jiang et al, 1999;Terai et al, 2000;Bett and Rasmusson, 2003;Du et al, 2010;Zhou and Bett, 2010;Du et al, 2011;Van Slyke et al, 2012;Shi et al, 2014;Shi et al, 2019). pH reductions within the physiological range (as low as pH 6.5) accelerated both the fast and the slow components of deactivation with a pKa of~6.8 (Bett and Rasmusson, 2003;Shi et al, 2019) with little effect channel conductance, and other voltage-dependent gating parameters (Jiang et al, 1999;Bett and Rasmusson, 2003;Shi et al, 2019).…”
Section: Targeted Modulation Of Herg Voltage Sensor Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of protons on gating have been thoroughly studied in Nav1.5 [25]. Although the identity of the residues involved in pH-dependent changes in gating have not been fully determined, structural studies in bacterial sodium channels and potassium channels suggest that acidic residues play a role [21,39]. Interactions of protons at the individual domains typically depolarizes the voltage-dependence, presumably via electrostatic interactions which hinder the outward movement of S4 voltage-sensors.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of extracellular protons can modulate both the VSD and the PD, depolarizing the voltagedependence of activation and blocking ionic current, respectively [18,19]. Acidification decreases peak sodium conductance by protonating the outer vestibule carboxylates [19,20], and likely by binding to negative charges in the VSDs, which destabilizes the outward conformation of the voltage-sensors [21,22].…”
Section: Introductionmentioning
confidence: 99%